2018
DOI: 10.1038/s41598-018-33501-z
|View full text |Cite
|
Sign up to set email alerts
|

Changing characteristics of the empathic communication network after empathy-enhancement program for medical students

Abstract: The Empathy-Enhancement Program for Medical Students (EEPMS) comprises five consecutive weekly sessions and aims to improve medical students’ empathic ability, an essential component of humanistic medical professionalism. Using a graph theory approach for the Ising network (based on l1-regularized logistic regression) comprising emotional regulation, empathic understanding of others’ emotion, and emotional expressivity, this study aimed to identify the central components or hubs of empathic communication and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 87 publications
3
20
0
2
Order By: Relevance
“…Further, in multicultural contexts, providers with a wide range of capabilities, such as trust and a high degree of self-reflection, could be achieved through robust training. 27 - 29 Therefore, policymakers must be aware of the need for education in cultural competency, not the least for ensuring the safety of patients from other cultural backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…Further, in multicultural contexts, providers with a wide range of capabilities, such as trust and a high degree of self-reflection, could be achieved through robust training. 27 - 29 Therefore, policymakers must be aware of the need for education in cultural competency, not the least for ensuring the safety of patients from other cultural backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the treatment of depressive symptoms, sustained emotional warmth from both parents has been shown to reduce significantly the severity of depressive symptoms experienced by male and female children and adolescents [81]. School-based programs targeting parent–student dyads or triads that focus on parental stress management skills [82] and emotionally attuned communication based on cognitive empathy [83, 84], offered during school vacations or on weekends, may help promote meaningful adolescent–parent communication.…”
Section: Discussionmentioning
confidence: 99%
“…The main method of doctor–patient communication in China is face-to-face communication, but the previous study reported similar for between screen-to-screen and face-to-face doctor–patient communication 60 ; additionally, researchers have documented that a “Photo Stories” presentation contributes to doctor–patient communication 61 , which all provide evidence of future communication methods in China. Importantly, Chinese medical staff must develop their communication skills, such as listening to patients, engaging them in shared decision making about health, and increasing awareness of performance-related feedback in medical practice 62 64 . Certainly, patients should also seriously adhere to individual literacy in health training, and with the participation of their families, they should alleviate their discomfort and vulnerability and feel open to express themselves 65 , 66 .…”
Section: Discussionmentioning
confidence: 99%